2021
DOI: 10.1007/s10584-021-03035-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring future global change-induced water imbalances in the Central Rift Valley Basin, Ethiopia

Abstract: Meteorological Agency of Ethiopia for providing the hydro-meteorological data. We thank the Oromia Irrigation Development Authority for providing the necessary data for the WEAP model.We also acknowledge the CORDEX-AFRICA databank for the projected future climate data. The first author would like to express his appreciation to the Indian Council for Cultural Relations for the financial support during his Ph.D. work and the facilities provided by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…56 (FAO-56). The MABIA approach has been largely used for water irrigation evaluation and management [28][29][30], as well as for assessment studies on the impact of climate change on water resources [31][32][33]. Figure 1 shows the organization chart of the proposed services, according to the required equipment.…”
Section: Equipment and Tools Required For The Suggested Ias Packagesmentioning
confidence: 99%
“…56 (FAO-56). The MABIA approach has been largely used for water irrigation evaluation and management [28][29][30], as well as for assessment studies on the impact of climate change on water resources [31][32][33]. Figure 1 shows the organization chart of the proposed services, according to the required equipment.…”
Section: Equipment and Tools Required For The Suggested Ias Packagesmentioning
confidence: 99%
“…A good description and understanding of rainfall and temperature trends is thus crucial for many studies related to irrigation (agriculture), climatology, and hydrology. Long-term trend analyses in rainfall and temperature are also important for rain-fed and irrigated agricultural areas, particularly for the ZLB, which is dominated by agricultural land [24]. It has been reported that both rainfall and temperature can impact water availability (Ziway Lake water level), irrigation water demand, water use efficiency, and productivity of the ZLB [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented hydrological responses of the ZLB to climate change with some studies based on only the historical period [21] and others based on projected areal rainfall and temperature over the large area [20]. While the previous studies focused on impact of climate change on hydrological responses of the basin [20,21,24], rainfall and temperature trends of the basin have not been analyzed in-depth. Therefore, indepth characterization, understanding, and trend analysis of rainfall and temperature both spatially and temporally are a vital procedure in assessing climate change impacts on freshwater resources availability, irrigation water uses, and water resources planning [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%